Scalix Mix Network - Vécsi, Ádám; Pethő, Attila (Acta Cybernetica, 2025)
Mix networks have now advanced to a level where they can compete in the domain of low-latency anonymous communication, owing to their "strong" anonymity design advantage. However, a few bottlenecks still exist, primarily because users are required to select the complete message path. This characteristic of mix networks hinders the implementation of load balancing and necessitates the use of an extensive shared database. To address this issue, we introduce Scalix, which presents a new topology featuring load balancers, modified path selection, and a mix package based on identity-based encryption and attribute-based encryption. Additionally, Scalix can serve as an anonymous return channel with minimal modifications.